Incidence and probable risk factors of stillbirth in Maternity Teaching Hospital in Erbil city - —–, Shahlaa Abd Alrahmman; Al alaf, Shahla K. (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objective: Death of an infant in utero or at birth has always been a devastating experience for the mother and of concern in clinical practice. The aim of this study was to determine the prevalence, probable risk factors and association of stillbirth with different maternal variables in Erbil Maternity Teaching Hospital. Methods: A cross-sectional design was used to determine the prevalence of stillbirth and a case control design was used to determine the probable risk factors and demographic characteristics of women with stillbirth in Maternity Teaching Hospital in Erbil city, Kurdistan region, Iraq, from April 1st, to December 31st, 2011.Three hundred seventy nine women having stillbirth were regarded as cases while 758 women delivering alive newborns were regarded as control group. Results: The prevalence of stillbirth during the period of the study was 20.4 per1000 total births. Macerated stillbirth was about four times higher than the fresh stillbirth. There were statistically significant differences between the cases and controls in relation to: maternal age (≥ 35 years), level of education, history of antenatal care visits, parity, medical diseases of the mother, congenital anomalies of the newborn, and history of previous stillbirth. In 65.4% of cases the probable cause of death was unexplained. Conclusion: The prevalence of stillbirth in the Maternity Teaching Hospital in Erbil is high in comparison to the rate in other countries. This could be due to high level of deliveries per day and lack of good follow up of patients during labour.